Novel Breast-Specific Long Non-coding RNA LINC00993 Acts as a Tumor Suppressor in Triple-Negative Breast Cancer - Guo, Shipeng; Jian, Lei; Tao, Kai; Chen, Chen; Yu, Haochen; Liu, Shengchun (Frontiers in Oncology, 2019)
Abstract: Background: Triple negative breast cancer (TNBC) was characterized by breast cancers that do not express estrogen receptor (ER), progesterone receptor (PR), or HER-2 genes. TNBC patients are associated with a shorter median time to relapse and death for the lack of available treatment targets. Long noncoding RNAs (LncRNAs) have been reported to play important role in the development of TNBC. We identified a novel breast specific long noncoding RNA LINC00993, but less was known about its expression pattern and functional role in TNBC. Methods: LINC00993 RNA expression was detected across different types of clinical breast cancer samples by using qRT-PCR. Bioinformatic methods “guilt by association” and gene set enrichment analysis (GSEA) were used to predict LINC00993 functions. Subcellular localization of LINC00993 in cells was detected by RNA fluorescence in situ hybridization (FISH). Effect of LINC00993 on cells growth was measured by plate colony formation assays，typical growth curve and In Vivo Tumor Model. Cell cycle analysis was done by Flow cytometry analysis. Key cell cycle regulators were detected by western blot. Results: LINC00993 was largely downregulated in TNBC and higher expression indicated better outcome. LINC00993 located mainly in nuclear. LINC00993 suppressed TNBC growth both in vitro and in vivo. LINC00993 was predicted to be involved in cell cycle pathways by using “guilt by association” and GSEA methods. Key cell cycle regulators like p16INK4A, p14ARF, p53, p21 were affected by LINC00993 overexpression. Conclusions: A new breast specific lincRNA LINC0093 was identified with a tumor suppressive feature and with prognostic value. This is the first research on LINC00993 function. Our results suggest that controlling LINC00993 level may be beneficial for breast cancer treatment.